2014
DOI: 10.1371/journal.pone.0113451
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Type II Epithelial Cell Dysfunction in Rat Experimental Hepatopulmonary Syndrome (HPS)

Abstract: The hepatopulmonary syndrome (HPS) develops when pulmonary vasodilatation leads to abnormal gas exchange. However, in human HPS, restrictive ventilatory defects are also observed supporting that the alveolar epithelial compartment may also be affected. Alveolar type II epithelial cells (AT2) play a critical role in maintaining the alveolar compartment by producing four surfactant proteins (SPs, SP-A, SP-B, SP-C and SP-D) which also facilitate alveolar repair following injury. However, no studies have evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…Similar findings are found in experimental HPS, where reductions in tidal volume, minute ventilation, and mean inspiratory flow rate, attributable to uneven distribution of alveolar ventilation and decreased mean alveolar cord length reflecting alveolar collapse, have been found . These functional and structural alveolar alterations are associated with increased apoptosis of AT2 cells and a resultant decrease in surfactant protein (SP) production (SP‐A, B, C, D) . Surfactant, a lipoprotein complex formed by AT2 cells, maintains alveolar integrity, prevents collapse, and regulates lung injury and inflammation.…”
Section: Pathogenesis Of Hps: Lessons From Experimental Modelssupporting
confidence: 61%
See 2 more Smart Citations
“…Similar findings are found in experimental HPS, where reductions in tidal volume, minute ventilation, and mean inspiratory flow rate, attributable to uneven distribution of alveolar ventilation and decreased mean alveolar cord length reflecting alveolar collapse, have been found . These functional and structural alveolar alterations are associated with increased apoptosis of AT2 cells and a resultant decrease in surfactant protein (SP) production (SP‐A, B, C, D) . Surfactant, a lipoprotein complex formed by AT2 cells, maintains alveolar integrity, prevents collapse, and regulates lung injury and inflammation.…”
Section: Pathogenesis Of Hps: Lessons From Experimental Modelssupporting
confidence: 61%
“…For instance, it is well recognized that HPS may coexist with intrinsic lung abnormalities, although the two processes have been considered distinct. More recently, subtle pulmonary function test abnormalities including lower forced expiratory volume in the first second (FEV1) and forced vital capacity, with a preserved ratio between the two, have been observed in patients with cirrhosis and HPS compared to those without, supporting that ventilation defects may contribute to gas exchange abnormalities in HPS …”
Section: Pathogenesis Of Hps: Lessons From Experimental Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…CX3CL1 and VEGF-A produced by circulating monocytes also contribute to angiogenesis, an IPVD pathogenetic factor [100,101]. Other factors, such as eNOS activation through endothelin-B receptor overexpression in the pulmonary endothelium [102][103][104] and a reduced production of alveolar surfactant proteins [105], should be considered. Although the role of inflammation in HPS pathogenesis is not as evident as in ARDS, all previous features suggest a role of BT-induced inflammatory response.…”
Section: Cirrhosis As a Systemic Inflammatory Multi-organ Diseasementioning
confidence: 99%
“…Moreover, type 2 alveolar epithelial cells can serve as stem cells to restore and turn over alveolar epithelial cells during lung injury and development1112. Many studies have shown that type 2 alveolar epithelial cell impairment leads to the development of lung diseases, including chronic obstructive pulmonary disease (COPD), acute respiratory distress syndrome ( ARDS ), and lung fibrosis13141516.…”
mentioning
confidence: 99%